Leadership handbooks of practical theology ; v. 1 - Berkley, James D. 1950- (Grand Rapids, MI Baker, 1992)
Contents v. 1 : Word and worship. Includes bibliographical references.
Reprints entitled : Leadership handbook of preaching and worship. Series name changed to : Leadership handbooks
Keywords: Theology, practical -- handbooks, manuals, etc